The Analysis of Type L Joint Precast Beam Concretea - A. Rudi Hermawan; Eka Sasmita Mulya (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
Research precast beam type L shape has produced strength of flexure where it was jointed at middle of span with L shape. Problem was about strength and deflection with joint of Type L shape. Aim of this research was determined strength of flexure such deflection and maximal load would be apllicated. Precast beam type L shape consist of two beam P1 and P2 were tested at two point load was applicated. This research have produced of data of precast beam P1 and P2. Precast beam P1 has deflection 28,44 mm at maximum load 11,21 Ton. Precast beam P2 has deflection 26,71 at maximum load 11,76 Ton. Except that data, has produced also chart of load versus deflection where precast beam type L shape has behavior less for ductility approximately du/dy 1,17, where deformation inelasticity was not seem. That occur because overlapping at joint of precast concrete at middle of span.